Child health problems and social determinants as predictors of postpartum depression: a cross-sectional study using 2023 Indonesia Health Survey data - Tri Wurisastuti; Santi Martini (Osong Public Health and Research Perspectives, 2026)
Objectives: This study examined the predictive role of child health problems and social determinants in postpartum depression (PPD), with the aim of supporting early screening strategies and more comprehensive maternal health policies.Methods: This cross-sectional study used secondary data from the 2023 Indonesia Health Survey, conducted by the Indonesian Ministry of Health. The analysis included 26,656 postpartum women aged at least 15 years who had given birth within the previous 24 months. PPD was assessed using the Mini International Neuropsychiatric Interview. Multiple logistic regression was used to analyze the data.Results: Child health problems were among the strongest factors associated with PPD in Indonesia. Having had an unplanned pregnancy was associated with higher odds of PPD (adjusted odds ratio [aOR], 3.90; 95% confidence interval [CI], 2.90–5.25; p